Cultura literaria y políticas de mercado - Gallego Cuiñas, Ana (De Gruyter, 2022)
The volume addresses three key aspects of today’s book culture: independent publishing, book fairs and literary festivals. Using an innovative theoretical framework (a literary "value criticism"), it offers an in-depth field study of some 349 independent publishers as well as 10 book fairs and festivals in Spain and the Americas to shed light on new production, circulation and reception processes in contemporary literary culture.